Upper Airway Obstruction as a Life-Threatening Emergency - Yuwono, Firman Khalif; Putri, Arsy Muchlisa; Azizah, Baiq Whafiq; Juwita, Septrajismi Dinda; Lestari, Rina (Jurnal Biologi Tropis, 2026)
Upper airway obstruction (UAO) is a life-threatening emergency characterized by partial or complete blockage of airflow through the upper respiratory tract due to mechanical obstruction or anatomical narrowing. It may occur acutely or chronically and result from congenital or acquired conditions, including infection, inflammation, trauma, malignancy, anatomical abnormalities, and foreign body aspiration. This study employed a literature review by analyzing publications retrieved from PubMed, Google Scholar, and ProQuest. Clinically, UAO presents with noisy breathing, including stertor and stridor, accompanied by dyspnea, dysphagia, hypoxemia, and respiratory distress. Children are particularly susceptible because of their relatively smaller airways. Diagnosis is established through history taking, physical examination, flexible laryngoscopy, and imaging studies such as neck radiography and computed tomography. Management focuses on restoring airway patency and maintaining adequate oxygenation through interventions including endotracheal intubation, tracheostomy, cricothyrotomy, high-flow nasal cannula, continuous positive airway pressure, and the Heimlich maneuver for foreign body airway obstruction. Delayed recognition and treatment may lead to respiratory failure, cardiac arrest, and increased morbidity and mortality. Therefore, early diagnosis and timely emergency management are essential to improve clinical outcomes.